Foreigners under Mao western lives in China, 1949-1976 - Hooper, Beverley (Hong Kong Hong Kong University Press, 2016)
"A pioneering study of the Western community during the turbulent Mao era. Based largely on personal interviews,memoirs, private letters, and archives, this book 'gives a voice' to the Westerners who lived under Mao. It shows that China was not as closed to Western residents as has often been portrayed."
'Foreign comrades' -- POW 'turncoats' -- Diplomats -- Correspondents -- 'Foreign experts' -- Students -- The Western community(ies).
Includes bibliographical references (pages 267-276) and index.
Keywords: Visitors, Foreign -- China -- History -- 1949-1976.; Visitors, Foreign -- China -- History -- 20th century; China -- History -- 20th century